The neuromedin U system: Pharmacological implications for the treatment of obesity and binge eating behavior - Luca Botticelli; Emanuela Micioni Di Bonaventura; Fabio Del Bello; Gianfabio Giorgioni; Alessandro Piergentili; Wilma Quaglia; Alessandro Bonifazi; Carlo Cifani; Maria Vittoria Micioni Di Bonaventura (Elsevier, 2023)
Neuromedin U (NMU) is a bioactive peptide produced in the gut and in the brain, with a role in multiple physiological processes. NMU acts by binding and activating two G protein coupled receptors (GPCR), the NMU receptor 1 (NMU-R1), which is predominantly expressed in the periphery, and the NMU receptor 2 (NMU-R2), mainly expressed in the central nervous system (CNS). In the brain, NMU and NMU-R2 are consistently present in the hypothalamus, commonly recognized as the main "feeding center". Considering its distribution pattern, NMU revealed to be an important neuropeptide involved in the regulation of food intake, with a powerful anorexigenic ability. This has been observed through direct administration of NMU and by studies using genetically modified animals, which revealed an obesity phenotype when the NMU gene is deleted. Thus, the development of NMU analogs or NMU-R2 agonists might represent a promising pharmacological strategy to treat obese individuals. Furthermore, NMU has been demonstrated to influence the non-homeostatic aspect of food intake, playing a potential role in binge eating behavior. This review aims to discuss and summarize the current literature linking the NMU system with obesity and binge eating behavior, focusing on the influence of NMU on food intake and the neuronal mechanisms underlying its anti-obesity properties. Pharmacological strategies to improve the pharmacokinetic profile of NMU will also be reported.